A new convolution variational boundary element technique for design sensitivity analysis and topology optimization of anisotropic thermo-poroelastic structures. Issue 1 (1st January 2020) - Fahmy, Mohamed Abdelsabour
Abstract: The main objective of this paper is to propose a new efficient time domain boundary element technique for design sensitivity analysis and topology optimization of anisotropic thermo-poroelastic structures. The spatial regularization scheme based on integration by parts is performed in Laplace domain in conjunction with time-domain convolution variational boundary element method (CVBEM). The generating optimization problem is solved using the Moving Asymptotes Method (MAM) with the adjoint variable method to obtain optimal material distribution, influence of anisotropy on the thermo-poroelastic stresses sensitivities. The results from the numerical model demonstrate the validity, efficiency and accuracy of the proposed technique.